Emission of xenon in the spectral range of 120 – 800 nm upon excitation by diffuse and spark discharges. (July 2021) - Panchenko, A.N.; Beloplotov, D.V.; Kozhevnikov, V.V.; Lomaev, M.I.; Sorokin, D.A.; Tarasenko, V.F.
Abstract: Xenon emission in the spectral range of 120 – 800 nm upon excitation by subnanosecond voltage pulses is investigated. Excitation is performed using diffuse and spark discharges in an inhomogeneous electric field at a xenon pressure ranging from 0.3 to 3 atm. It is shown that xenon excitation by a series of successive 0.7-ns voltage pulses with a pause of 30 ns leads to a decrease in the second-continuum radiation intensity by the second and subsequent voltage pulses and an increase in the first-pulse afterglow intensity. It is confirmed that in the case of a pulsed diffuse discharge, the second continuum of xenon dimers, which is used to generate laser and spontaneous radiation in the VUV spectral region, makes the largest contribution to the radiation energy. Broadband radiation in the visible range ( λ > 400 nm) is found to occur when the discharge is constricted. The obtained results indicate that the influence of the dynamic displacement current on the pin-diode caused a measurement error in the papers by V.I. Baryshnikov et al., who did not record the second-continuum radiation from xenon excited by a short homogeneous discharge.